2002
DOI: 10.1590/s0103-90162002000400007
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bemisia tabaci (Gennadius,1889) biotype B on Lycopersicon spp. genotypes

Abstract: Whiteflies are phytophagous insects, whose nymphs and adults suck the phloem sap, causing direct damage due to host plant weakness. In tomato (Lycopersicon spp.) crops, they are important vectors of limiting fitoviruses. The objective of this study was to determine the effects of Lycopersicon spp. genotypes on Bemisia tabaci (Gennadius, 1889) biotype B development under greenhouse conditions. The evaluated genotypes were LA462 (and Santa Clara (L. esculentum). LA716 was non-preferred for oviposition by the whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Adults of both species survived a very short time on Ye-Sheng and oviposited very few eggs where after 24 h almost all adults died. This is due to the presence of a high number of glandular trichome Type IV on Ye-Sheng leaves [ 58 , 65 , 69 , 70 ]. During experimentation, it was found that whitefly adults entrapped in sticky exudates released from glandular trichomes type IV and subsequently died [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adults of both species survived a very short time on Ye-Sheng and oviposited very few eggs where after 24 h almost all adults died. This is due to the presence of a high number of glandular trichome Type IV on Ye-Sheng leaves [ 58 , 65 , 69 , 70 ]. During experimentation, it was found that whitefly adults entrapped in sticky exudates released from glandular trichomes type IV and subsequently died [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%